THE PROTECTION OF PRISONERS OF WAR IN THE ISRAEL-PALESTINE CONFLICT BASED ON INTERNATIONAL HUMANITARIAN LAW AND ISLAMIC LAW - Jawanta, Hira Syaud (Universitas Wijaya Putra, 2024)
This study examines the treatment of prisoners of war (POWs) in the Israel-Palestine conflict through the frameworks of International Humanitarian Law (IHL) and Islamic law. Both legal systems emphasize humane treatment for POWs; however, reports indicate severe rights violations against Palestinian detainees in Israel, including torture and inhumane conditions. Conversely, Hamas is reported to treat POWs by relatively higher standards. By integrating IHL and Islamic principles, this research provides a novel perspective on legal and ethical dimensions in POW treatment amid a prolonged conflict. Findings underscore the urgent need for enforcing humane standards to curb human rights abuses. Although based on secondary data, the study emphasizes the importance of further primary-source research and calls for enhanced international monitoring and strict adherence to IHL to ensure legal protections for POWs in active conflict zones.